Pendampingan dan Pelatihan Pembuatan Video Kampanye Remaja Anti Narkoba di Desa Purworejo Kecamatan Sragi Kabupaten Pekalongan - Jaya Maulana; Nur Lu’lu Fitriyani; Teguh Irawan; Diva Alya Anggraeni; Salsabilla Salsabilla; Agustina Ayu Prasyanti; Nirmala Falujatunnisa; Keisya Ayu Nuansa Safitri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Indonesia is in a state of emergency due to narcotics and illegal drugs (narcotics). By 2024, the prevalence of drug abuse in Indonesia had reached 3.3 million people, dominated by the younger generation, especially teenagers aged 15 to 24. Drug abuse was the highest or most common case in Pekalongan Regency throughout 2024, with 29 cases. This is based on data from the Pekalongan Police Department regarding all cases uncovered over the past year. Drug cases in Pekalongan Regency were spread across several sub-districts, one of which was Sragi Sub-district. The purpose of this Community Service (PKM) activity was to provide education on the dangers of drug abuse using lectures, jigsaw puzzles, and role-play methods. Results: This activity took place on Sunday, March 5, 2023, at Purworejo Public Elementary School. The community service participants consisted of four female cadres and 16 adolescent members of the youth integrated health post (Posyandu) in Purwoharjo Village, Sragi Sub-district.